PENGARUH PEMBERIAN REWARDS DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN DI RSI MUHAMMADIYAH KENDAL - Lena Riyanti; Susanto Susanto; Qurratul 'Aini (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
Work performance is the result of the quality and quantity achieved by an employee in their duties performing. Accomplishments can be achieved by increasing the satisfaction that can be realized giving Rewards proportionally and fair and to create a conducive working environment. Harmonious relationship that exists between a leader-employee is also needed among employees with one another to create a conducive working environment. The results of preliminary studies on Muhammadiyah Islamic Hospital of Kendal seen a lot of indiscipline and delay the return of earlier of employees and the number continues to increase. This research was quantitative descriptive with cross sectional research planning. Research populations were employees / workers of Muhammadiyah Islamic Hospital of Kendal. The sampling technique in this research is using proportions stratified random sampling with the number of sample as much as 137 people. Retrieval of data using questionnaires. Analysis of data using multiple linear regression analysis. There is an effect of giving rewards to employees' achievement of Muhammadiyah Islamic Hospital of Kendal (p<0,05). There is an influence of work environment of employees' achievement on Muhammadiyah Islamic Hospital of Kendal (p<0,05). There is an effect of giving rewards and working environment of employees' achievement on Muhammadiyah Islamic Hospital of Kendal.